Participatory Budgeting in spain. A case study: the Citizen Budgeting of Logroño - Pineda Nebot, Carmen; Fernández Rodríguez, Carlos Jesús (FCL-UNESP Laboratório Editorial, 2009)
In the last years Participative Budgeting has turned itself into a theme of central debate in local politics. The main goal of this article is to analyze one of these experiences of participatory budgeting: the Citizen Budgeting of Logroño. The present work combines both an empirical part in which the main results of the evaluation were accomplished from the experience with a theoretical reflection, trying to evaluate through many indicators the way how citizenship has been engaged with the “municipal government”. The interest of the experience lies on the fact that it was started by a government of conservative ideals (the Popular Party), something not very frequent. The research consisted of several interviews with the main participants of the process as well as the analysis of the documents related to the municipal budget.